Participatory Integrated Climate Services for Agriculture (PICSA) as part of Rwanda Climate Services for Agriculture: Findings from quantitative evaluation of 2017/18 PICSA implementation - Clarkson, Graham; Dorward, Peter; Nsengiyumva, Gloriose; Kagabo, Desire (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Participatory integrated Climate Services for Agriculture (PICSA) is being implemented in multiple districts across Rwanda as part of the Rwanda Climate Services for Agriculture project. This report presents findings from the evaluation of PICSA implementation across ten districts in the third year of the project. PICSA training of Farmer Promoters took place in late 2017 ahead of implementation with farmer groups. This document reports on a quantitative survey of 502 randomly selected trained farmers. The quantitative evaluation took place in May 2018 after the season had finished and respondents had been able to harvest. Results from the quantitative survey show that most of the farmers were trained on the PICSA elements that are implemented ‘long before the season’. Almost all respondents were trained in the seasonal forecast and two thirds received short term forecasts during the season. 98% of farmers had made changes in their farming or other livelihood activities as a result of PICSA training. More farmers made changes in crops (96% of respondents) than livestock (29%) and other livelihoods (6%). Men made an average of 2.4 changes per farmer and women 2.1. The most popular types of changes made in crops were changing the management of land (50%), changing the amount and / or type of inputs used (35%); changing planting date (27%); growing a new variety of a crop they already grow (25%); and growing a new crop (20%). The most popular change in livestock enterprises were starting a new enterprise (15%), followed by changing the management of a livestock enterprise (11%) and increasing the scale of a livestock enterprise (6%). Regarding other livelihoods 4% of respondents had started a new enterprise, 1% had increased scale and 1% had changed management of livelihood enterprises. Regarding the effects of the changes farmers had made as a result of the PICSA training, 92% of farmers reported that the decisions they had taken had improved their household food security. 86% reported that they had improved household income, 81% that they had been better able to provide for family healthcare and 74% that they had found it easier to pay their children’s school fees. Respondents reported that as a result of the PICSA training and the effects of the changes they had made that they are more confident in planning and decision making (93%), better able to cope with bad years caused by the weather (76%) and had improved their social standing within their households (92%) and within their wider community (91%). PICSA is an integrated approach that enables individual farmers to study their own resources and farming systems, the climatology of their area, identify, evaluate and plan appropriate options to cope with and adapt to climate variability and change. The results of this study show that this integrated approach has continued to stimulate innovation and change in farming communities as it has been scaled across Rwanda.